Opening the Limits of Artistic and Social Expression: From the Individual Gesture to the Open Work - Cuenca Ramón, Lorena (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The 20th century marked a before and after in the Art. Fundamentally, the emergence of the avant-garde brought new ideals that allow the open work approach. Therefore, from the current context of the 21st century, we ask ourselves: How does the Art express this idea of open work? And how does the Art of today manage to expand towards social and communicative pretensions that involve the viewer in new forms of participation? It is because we show different examples, which tell us how the situation of the author and the viewer in front of the work has developed.